Implementasi Sapa Pagi dalam Pembinaan Etika Sosial Siswa SDN 52 Kota Bengkulu - Dilla Dwi Udiyana; Puspa Djuwita; Pebrian Tarmizi (Universitas Bengkulu, 2019)
This study aims to describe the implementation of morning greetings in the development to sosial ethics on cultural behavior 5S (smile, greetin, greeting, polite, and courteous). The type of research used is descriptive quantitative research with descriptive method and percentage technique. The subjects of the study were VB students of 26 student.The research instrument is qualitative research that is self researcher, assisted by observation and interview guides plus quesionnaire sheect. Technique analysis of observation data and interview in narration while quesionanaire data(tecnique ercentage). From the result of research with the detail of the research that carry out the 5S culture well as many as 18 student(69,23%),able to undestand the implementation of sapa thismorning to prove the existence of the relationship of the morning greeting and behavior of the student, as many as 24 student(92,30%)23 students (96,15%)were able to have greeting attitude,as many as 23 student(88,46%)23 students(88,46%) able to have polite attitude. So the cunclusion of this study is that it can be said that the students of VB class have been implementing culture 5S well.